Nitrosative Stress Molecules in Multiple Sclerosis: A Meta-Analysis - Moritz Förster; Christopher Nelke; Saskia Räuber; Hans Lassmann; Tobias Ruck; Maria Pia Sormani; Alessio Signori; Hans-Peter Hartung; Patrick Küry; Sven G. Meuth; David Kremer (Biomedicines, 2021)
Multiple sclerosis (MS) is an immune-mediated disease of the central nervous system of unknown etiology. As it is still a diagnosis of exclusion, there is an urgent need for biomarkers supporting its diagnosis. Increasing evidence suggests that nitrosative stress may play a pivotal role in the pathogenesis of MS. However, previous reports supporting the role of nitrosative stress molecules as disease biomarkers are inconsistent overall. We therefore systematically analyzed the existing literature to compare the serum and cerebrospinal fluid (CSF) levels of nitrite/nitrate in MS patients with those in patients with noninflammatory other neurological diseases (NIOND) and healthy controls (HC), respectively. We searched the PubMed database and included original articles investigating nitrite/nitrate levels in MS patients and NIOND patients or HC based on predefined selection criteria. Effect sizes were estimated by the standardized mean difference using a random effects model. Our results suggest that MS is associated with higher nitrite/nitrate levels within the CSF compared with patients with NIOND (SMD of 1.51; 95% CI: 0.72, 2.30; p = 0.0008). Likewise, nitrite/nitrate in the CSF of MS patients trends towards increased levels compared with those of HC but does not reach statistical significance (SMD of 3.35; 95% CI: −0.48, 7.19; p = 0.07). Measurement of nitrite/nitrate in the CSF might be a valuable tool facilitating the differentiation of MS and NIOND. Further studies with more homogeneous study criteria are needed to corroborate this hypothesis.